1980
DOI: 10.1007/978-3-642-67637-6
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Processes in Plant Ecology

Abstract: This work is subject to copyright. All rights are reserved, whether the whole or part of the material is concerned, specifically those of translation, reprinting, re-use of illustrations, broadcasting, reproduction by photocopying machine or similar means, and storage in data banks.Under §54 of the German Copyright Law where copies are made for other than private use, a fee is payable to the publisher, the amount of the fee to be determined by agreement with the publisher. © by Springer-Verlag Berlin· Heidelbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
1
3

Year Published

1984
1984
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(80 citation statements)
references
References 243 publications
(425 reference statements)
3
72
1
3
Order By: Relevance
“…Finally, Osmond et al (1980) presented an analysis similar to that given here, but reached different conclusions based on two inappropriate assumptions. They found that leaves acclimated to a given irradiance have a greater 24 h carbon balance at that irradiance than leaves acclimated to another irradiance, regardless of whether photosynthesis is expressed per unit area or per unit mass.…”
Section: Photosynthetic Light Responsementioning
confidence: 71%
See 1 more Smart Citation
“…Finally, Osmond et al (1980) presented an analysis similar to that given here, but reached different conclusions based on two inappropriate assumptions. They found that leaves acclimated to a given irradiance have a greater 24 h carbon balance at that irradiance than leaves acclimated to another irradiance, regardless of whether photosynthesis is expressed per unit area or per unit mass.…”
Section: Photosynthetic Light Responsementioning
confidence: 71%
“…Leaf construction costs per unit area should scale like leaf biomass per unit area, provided the leaves in question do not vary much in composition (Osmond et al 1980); if the latter were true, P / C would be directly proportional to photosynthesis per unit leaf mass. However, leaf composition does vary with irradiance, notably in the fraction devoted to soluble protein (Bjorkman 1981) and nitrogen (Field and Mooney 1986).…”
Section: Photosynthetic Light Responsementioning
confidence: 99%
“…This was accompanied by a decrease in the chl content and in the chl a/b ratio. As the water content of the leaves had also decreased dramatically, it seems that these changes were at least partly due to water stress, although opinions difiFer somewhat concerning the eifect of water stress on the chl content and chl a/b ratio, on the chlorophyll-protein complexes and on the chloroplast ultrastructure (see Osmond, Bjorkman & Anderson, 1980). Moreover, many effects of water stress, such as a possible decrease in the chl content (Freeman & Duysens, 1975;Alberte, Thornber & Fiscus, 1977) or increase in the number and size of plastoglobuli (Vapaavuori, Korpilahti & Nurmi, 1984) are the same as the changes seen during ageing and senescence of the leaves (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the air temperature was over 30°C, the quantum yield in C4 plants was slightly higher than that in C3 plants (Ehleringer and Pearcy, 1983). When photorespiration was inhibited by high CO 2 and/or low O 2 , C4 plants had about 30% lower quantum yields than C3 plants because they used two additional ATP molecules in the C4 pathway for fixation of one molecule of CO 2 to form carbohydrate (Osmond et al 1980;Xu and Shen, 2000).…”
Section: Internal Factorsmentioning
confidence: 99%